The Role of AI as a Communication Mediator in the Learning Process - Muhammad Ridha; Mamdukh Budiman; Junaidi; Audy Rifdah Widyastuti; Suryanti; Kamsar; Aliyah (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2026)
ABSTRACT The development of Artificial Intelligence (AI) has brought significant changes to digital learning practices, particularly in the way educational communication takes place. This study aims to examine the role of AI as a communication mediator in the learning process through a synthesis of Scopus-indexed scientific literature. This study uses a literature review approach by analyzing 40 scientific articles discussing the use of AI in education, including generative AI, educational chatbots, intelligent tutoring systems, pedagogical agents, and social robots. The analysis was conducted thematically to identify patterns of AI's role in mediating learning communication. The results show that AI acts as a communication mediator through four main functions: (1) an instructional dialogue mediator that facilitates two-way interaction and cognitive scaffolding; (2) a feedback and learning regulation mediator that provides instant and dialogic responses; (3) a mediator of social and collaborative communication that supports group interaction and inclusive learning; and (4) a mediator of personalized learning communication that tailors the style and content of interactions based on learners' needs. These findings confirm that AI functions not only as a technological tool but also as a non-human communicative actor that shapes the structure, meaning, and dynamics of pedagogical communication. This research contributes to the development of educational communication studies by offering a conceptual perspective on AI as a communication mediator in learning. Its practical implications include the importance of pedagogical and ethical design in AI integration so that the communication mediation role performed by AI is aligned with educational goals and values. Keywords: artificial intelligence, educational communication, communication mediator, digital learning, literature review